THE DEVELOPMENT OF BASKET BALL GAME LEARNING MODEL THROUGH MODIFICATION OF FACILITIES AND INFRASTRUCTIVES IN JUNIOR HIGH SCHOOL STUDENTS - Taher, Tedy Tanjung
This study aims to produce a model of learning products through the modification of basketball game facilities and infrastructure are valid, practical, and effective. Methods in this study are Research and Development (R & D) in the order of 1) Needs Analysis, 2) Initial Product, 3) Initial Product Validation, 4) Initial Product Revision, 5) Draft Small Group Test Products, 6) Product Revision after Test Try Small Group, 7) Large Group Product Trial Draft, 8) Large Group Trial, 9) Big Group Trial Revision, and 10) Final Items. The result of small group experiment on filling the student questionnaire covering cognitive, psychomotor, affective, and motivational aspects is the average frequency distribution value of 72.9%, the shot rating includes the old learning model basket ball of 66.51%, the shot rating students of new learning model increased by 71,7%, meanwhile large group questioning test was obtained by frequency distribution equal to 78,4%, appraisal of basketball with old learning model equal to 68,20%, new student learning shoot increased by 72,30 %. So from the results of the basketball learning model products through having a good criteria of validity, practicality and effectiveness. Based on the above explanation has been found basketball learning model through the modification of basketball game facilities and infrastructure the implications of the research have valid, practical, and effective criteria so that it can be applied in the junior high school level.